Examining community perspectives on integrated service delivery for tuberculosis, mental health and substance use disorder in Nigeria: A qualitative study - Martin Njoku; Charles Nwafor; Chinwe Eze; Okechukwu Ezeakile; Anthony Meka; Ngozi Ekeke; Iyama Francis; Daniel Egbule; Joseph Chukwu; Charles Esekhaigbe; Chijioke Osakwe; Edmund Ndudi Ossai; et al. (PLoS ONE, 2026)
Background The concept of integrated service delivery was the focus for the envisaged essential health care under one roof. Despite being the central focus of essential health under one roof and a crucial principle of primary health care, relatively little is known about community perceptions on integrated service delivery in low-and middle income countries. This study was designed to examine community perspectives on integrated service delivery for tuberculosis (TB), mental health (MH) and substance use disorder (SUD) in Nigeria. Methods This was a community-based cross-sectional study design using qualitative data collection methods. Data was obtained from the participants using a pre-tested focus group discussion (FGD) guide. Data was collected from three states in Nigeria including Anambra, Enugu and Nasarawa states. Twelve FGDs were conducted among 116 participants who were beneficiaries of the integrated service delivery for TB/MH/SUD and their relatives. There were four FGDs in each state. The discussions were conducted separately for patients and relatives and for male and female participants. QDA Miner Lit v2.0.6 was used in the thematic analysis of data. Results Almost all the participants perceived the three disease entities as being linked to one another hence it may not be the best to manage each condition in isolation thus supporting the integrated approach. The participants noted the positive provider attitude of the healthcare workers involved in the program. They were of the opinion that integrated service delivery (ISD) has improved the awareness of the three disease entities among the populace. Most of the participants expressed their willingness to patronize integrated service delivery at the community level from trained lay health workers. This willingness to patronize was predicated on the approval of the program by the government. Conclusions Positive provider attitude of health service providers will be a good boost to efforts to improve health service delivery in Nigeria including integrated service delivery. Government has a key role to play in community acceptance of health service delivery programs. The program increased the awareness of the three diseases among the people. Thus, increasing the community awareness of TB, mental health and substance use disorders should be prioritized. Adopting the integrated service delivery approach will be of value. Consideration should be made on the use of lay health workers for the delivery of such services at the community level especially in rural areas. There is a need to incorporate community perspectives on the value, benefits, barriers and acceptability of integrated service delivery into policies guiding TB/MH/SUD integration in Nigeria.